Root characteristics of spring wheat under drip irrigation and their relationship with aboveground biomass and yield - Rui Chen (Nature Portfolio, 2021)
Abstract The objectives of this two-year field experiment were (1) to study the effect of irrigation frequency and irrigation amount on the root characteristics of drip-irrigated spring wheat (Triticum aestivum L.) and (2) to determine the relationship between these root characteristics and aboveground biomass and yield. A split-plot design was used with two wheat cultivars (Xinchun 6 and Xinchun 22). The irrigation treatments consisted of three irrigation intervals (D1, 13 d; D2, 10 d; and D3, 7 d) and three water amounts (W1, 3750 m3/ha; W2, 6000 m3/ha; and W3, 8250 m3/ha). The results showed that root length density (RLD) and root weight density (RWD) were greater at 0–20 cm than at 20–40 cm at flowering. The RLD was greater in D1 and D2 than in D3 in the shallow soil layer and did not differ among the treatments with different irrigation frequencies in deep soil. The RLD at the 0–20 cm depth of W3 was 17.9% greater than that of W2 and 53.8% greater than that of W1, and the RLD trend was opposite at the 20–40 cm depth. The root–shoot ratio was significantly higher in D2 than in the other treatment, whereas the RLD, RWD, leaf Pn and LAI were significantly greater in D3. Leaf Pn and LAI both increased as the irrigation amount increased. Regression analysis showed a natural logarithmic relationship between RWD and aboveground biomass (R2 > 0.60, P < 0.05) and binomial relationships of the RWD at 0–20 cm depth (R2 = 0.43, P < 0.05) and the RLD at 20–40 cm depth (R2 = 0.34, P < 0.05) with grain yield. We found that with the optimum irrigation amount (W2), increasing drip irrigation frequency can increase wheat root length and root weight and aboveground biomass accumulation, thereby improving yield and water use efficiency.